Kidney Disease – Bangladesh Perspective - Alam, Muhammad Rafiqul (Bangladesh Journal of Medicine, 2023)
In Bangladesh, most patients with Chronic Kidney Disease (CKD) are diagnosed in the advanced stages of the disease, which leads to a high demand for kidney transplantation and dialysis services.Several studies suggest prevalence rate of CKD 6–18%; of them 11% were in stage III–V.Every year 35,000-40,000 new cases of kidney failure.Every year >20,000 chronic kidney failure patients die as they cannot afford dialysis or kidney transplant.73% treatment cost is out of pocket in Bangladesh.The cost of hemodialysis per session varies from 400- 4500 BDT (USD 4-45) depending on institute.Even the ultra-poor patients who take dialysis at the rate of BDT 500 (USD 5) per session have to spend a minimum of BDT 20,000 (USD 200) per month only for the treatment cost. 40% patients discontinue dialysis after 3-4 months due to financial constraint. The existing facilities can hardly accommodate 9000–10,000 new patients, which means RRT isnot available for 70–75% of ESRD patients.Annually dialysis is done on >18,000 kidney patients across the country.80% of the total kidney-related deaths are caused due to insolvency to continue treatment.Currently >90% of dialysis patients are receiving Hemodialysis.Initiatives are taken to make CAPD more accessible, but high cost of PD fluid & lack of trained personnel remains as major barriers. Challenges are there in providing Nephrocare.There is insufficient number and uneven distribution of trained medical & allied health professionals, lack of proper referral system & follow-up & lack of laboratory facility in many areas, particularly in rural setup.Absence of insurance coverage for kidney dialysis & transplant treatment.Absence of patient support group & their participation in policy making process. To overcome the challenges we have to ensure affordable & equitable access to kidney care for people living with CKD through Public & Public Private Partnerships. Protection from out-of-pocket healthcare expenditure through universal health coverage to provide insurance coverage for CKD patients and Subsidized treatment for dialysis & kidney transplant.Expansion of Fellowship program to develop more Nephrologists & training facility/ centers to develop more allied health professionals.Facilitating research for kidney disease with technical and financial support.Improve screening to ensure timely diagnosis and prevent CKD related complications. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 179-180